2014
DOI: 10.1155/2014/325098
|View full text |Cite
|
Sign up to set email alerts
|

Fetomaternal Outcome in Severe Preeclamptic Women Undergoing Emergency Cesarean Section under Either General Or Spinal Anesthesia

Abstract: This prospective observational study compared the effects of general and spinal anesthesia in 173 severe preeclamptic women undergoing emergency cesarean section. 146 (84.5%) patients underwent spinal anesthesia (SA) and 27 (15.5%) patients had general anesthesia (GA). Most of the patients were primigravid and nulliparous. Intraoperatively SA group required more intravenous fluid and vasopressor support, while GA group required more preoperative labetalol injection for blood pressure control. Overall 13.3% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 19 publications
4
28
1
Order By: Relevance
“…This is consistent with the identification of a significant level of risk for neonatal encephalopathy recently published by Walsh et al 17 in the analysis of a cohort of 76 810 term singleton neonates. Our findings regarding the increase in the risk associated with GETA as well as with ECS are also consistent with other studies addressing these conditions 4 18 19…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the identification of a significant level of risk for neonatal encephalopathy recently published by Walsh et al 17 in the analysis of a cohort of 76 810 term singleton neonates. Our findings regarding the increase in the risk associated with GETA as well as with ECS are also consistent with other studies addressing these conditions 4 18 19…”
Section: Discussionsupporting
confidence: 92%
“…This result shows GA groups had relatively elevated pulse rate and blood pressure when compared with SA group. This finding is in line with prospective study conducted in India, retrospective study conducted in Pakistan and randomized controlled study conducted in India which found prevalence of uncontrolled hypertension and tachycardia to be higher among GA group when compared with SA group (AhsanUl-Haq, 2004;Chattopadhyay et al, 2014;Denu et al, 2015). This result could be explained by the exaggerated response of patients' to laryngoscopy after intubation of endotracheal tube.…”
Section: Discussionsupporting
confidence: 84%
“…There was no significant difference in the birth weight between the two anesthetic procedures for LSCS which was consistent with other studies. 15,29 There was a significant difference in the number of NICU admissions between the groups. Similar observations were made in several other previous studies.…”
Section: -6 >7mentioning
confidence: 89%
“…Other studies have also reported a higher incidence of respiratory distress in the neonates following CS under GA increasing the need for resuscitation and endotracheal intubation compared to the procedure under RA. 11,13,28,29 Majority of the subjects from both the groups had normal APGAR scores (>7). However, there was a significant difference in the mean score between the groups.…”
Section: -6 >7mentioning
confidence: 97%
See 1 more Smart Citation